2013
DOI: 10.2215/cjn.07300712
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia and Treatment-Related Infectious Complications in ANCA-Associated Vasculitis

Abstract: SummaryBackground and objectives ANCA-associated vasculitis (AAV) is treated with potent immunosuppressive regimens. This study sought to determine risk factors associated with infections during first-intention therapy.Design, setting, participants, & measurements This retrospective study involved two separate cohorts of consecutive cases of AAV seen from 2004 to 2011 at two university hospitals. The following were assessed: vasculitis severity; therapy; and periods with no, moderate (lymphocyte count, 0.3-1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 33 publications
4
70
1
8
Order By: Relevance
“…Lymphocytopenia was defined according to common definitions (L<1000·10 9 /L). [16][17][18] We assessed patient characteristics, for example, history of stroke, cardiovascular comorbidity, nicotine or alcohol abuse, by standardized mailed questionnaires. We conducted a semiquantitative phone interviews-performed by physicians trained and certified for data collection on disability and quality of life-with patients or their closest relatives if the questionnaire did not return within 2 to 4 weeks.…”
Section: Parameter Acquisitionmentioning
confidence: 99%
“…Lymphocytopenia was defined according to common definitions (L<1000·10 9 /L). [16][17][18] We assessed patient characteristics, for example, history of stroke, cardiovascular comorbidity, nicotine or alcohol abuse, by standardized mailed questionnaires. We conducted a semiquantitative phone interviews-performed by physicians trained and certified for data collection on disability and quality of life-with patients or their closest relatives if the questionnaire did not return within 2 to 4 weeks.…”
Section: Parameter Acquisitionmentioning
confidence: 99%
“…Infection was the leading cause of death in this cohort as in other studies [12] and all deaths attributable to severe infections occurred early in the treatment course (within the first 6 months) [3,4,6], when disease activity was greatest, and the highest doses of corticosteroids were used coupled with cyclophosphamide [4,5,8,10,14]. Another study also reported significantly higher rates of severe infections associated with severe lymphopenia (p < 0.001), independent of other risk factors [10].…”
Section: Discussionmentioning
confidence: 73%
“…Another study also reported significantly higher rates of severe infections associated with severe lymphopenia (p < 0.001), independent of other risk factors [10]. In addition, lower estimated glomerular filtration rate (eGFR) and longer duration of glucocorticoid use was also shown to be associated with poorer outcomes [8,10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged corticosteroid treatment has been identified as one of the underlying factors [9]. Biological therapies increase the possibility of serious infections, with varying effects on the safety profile depending on their mechanism of action.…”
Section: Immunosuppressive Treatments and Infectionsmentioning
confidence: 99%